Religious Pluralism and New Political Identities in Latin America - Parker-Gumucio, C (SAGE Publications Ltd, 2016)
The role of religion in Latin American politics can no longer be interpreted with reductionist schemes. The faithful-citizens-are combining faith and politics in unprecedented ways, and churches and denominations are no longer factors of political identity. The reconfiguration of new social and political movements interweaves complex linkages with the religious. The transformations of the political field and especially of democratic processes have reshaped identities in a context of increasing religious and cultural diversity with relatively less Catholic presence and greater Evangelical presence. Institutional secularization and religious pluralism seem to go hand in hand with a new cleavage between religion and politics © 2016 Latin American Perspectives.